Egypt and Russia: how to anticipate the restoration of cooperation in tourism - V. V. Khozhempo; Salim Muhammad Salah El Din (Путеводитель предпринимателя, 2020)
The article determines the prospects for recovery of the attractiveness ofEgypt as a tourist region for Russian tourists. The development of the tourism industry ofEgypt and its role in the economy of the country were analyzed. The most violent, geographically, tourist passenger traffic were educed. The negative effects of aviation disasters over the Sinai on the tourism industry and the economy ofEgypt as a whole were determined. A program to improve the safety of stay of tourists in the country was suggested.